EFFECTS OF ANXIETY AND DEPRESSION ON ACADEMIC PERFORMANCE OF UNDERGRADUATES: A STUDY OF EBONYI UNIVERSITY, ABAKALIKI - Ude, Chukwu Dominic C.; Ofoke, Sunday M. (EBSU Journal of Social Sciences and Humanities, 2022)
This study investigated the effects of anxiety and depression on academic performance among Ebonyi State University undergraduates. Eighty (80) undergraduates were drawn from the Department of Psychology. The participants in the study were measured using State Trait Anxiety Inventory (STAI) and Beck’s Depression Inventory (BDI) standardised for Nigerian use. The rating scale, tagged Student Academic Performance Rating Scale (SAPRS) was designed to enable the researcher evaluate the academic performance of students taught by the lecturer’s from 2007/2008 to 2011/2012 school years. The two-way analysis of variance (ANOVA) with unequal sample size was used to test the two hypotheses. The results indicate that high anxiety and depressed undergraduates performed poorly than low anxiety and depressed undergraduate. F(1,76)=792.8, P<0.001 there was significant interaction effect of anxiety and depression on academic performance.